POESIA FALADA: COMO A MULHER POETA SE DIZ NOS SLAMS - Schulz, Rafaela Tristão (2024)
This research aims to analyze, based on the production conditions of slams, how women express social issues related to femininity through spoken poetry. To achieve this, drawing on the theoretical-methodological framework of Materialist Discourse Analysis, and using empirical data obtained through observation, the study utilizes excerpts taken from videos on the YouTube platform titled "Receba a delicadeza" by poet Tawane Theodoro, and "Receita" by poet Mariana Felix, both published in "Slam Resistência" and "Slam da Guilharmina," located in the city of São Paulo. The specific objectives include understanding the functioning of slams, exploring the thematic axes present in the speeches, analyzing them in operation, identifying dominant discursive formations, analyzing their effects of meaning, and presenting how the body is performed and characterized as an instrument of resistance. Through these objectives, the research seeks to understand how these women give voice to social issues related to femininity, such as violence against women, and how they resist it. The analytical chapters aim to address these objectives. Thus, the first chapter seeks to demonstrate how Poetry Slam emerged and how the poetic event occurred after its arrival in Brazil. Conversely, in the second chapter, the methodological corpus constituting this research is examined, including the chosen corpus and the components of analysis. In the third chapter, the stereotype of the delicate woman is explored through slam poetry, examining how these discourses are reproduced by memory and how the body moves within discourse to oppose patriarchal discourses through resistance in their speech. Finally, in the last chapter of analysis, the aim is to understand how metaphor and ideology allow the poet to convey her ideologies through poetry, exposing her experiences and using her body and speech to empower herself and resist discourses that still resonate in society, whether in women's decisions, their bodies, or motherhood. In particular, it highlights how an abusive relationship leaves marks on a woman, especially in her speech.